STRATEGI KEBERLANGSUNGAN INDUSTRI PARIWISATA DI OBJEK WISATA DANAU TOBA PADA MASA PANDEMI COVID-19 (Studi Kasus di Kelurahan Tuktuk Siadong, Kecamatan Simanindo, Kabupaten Samosir, Provinsi Sumatera Utara) - Sihite, Grace Yellow; Nugroho, Wahyu Budi; Krisna Aditya, I Gusti Ngurah Agung (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
The focus of this research is to provide an understanding of the strategies carried out by tourism business actors in Tuktuk Siadong which is in Lake Toba tourist area during the Covid-19 pandemic. The method in this research is a qualitative research method. The theory used in this study is the theory of rational choice by James S. Coleman. The results of this study explain that the Covid-19 pandemic has an impact on tourism activities in the Tuktuk Siadong area. Restrictions on the movement of people affect the number of tourist visits to decrease drastically. The strategies carried out by the tourism industry are different, namely cutting the number of employees, utilizing digital platform innovations for online and offline promoyions, discounting prices, marketing delivery systems and increasing resources by farming and raising livestock. Other efforts are disconnecting the wifi network, reducing electricity use, reducing expenses and household needs.